Evidence of nerve agent VX exposure in rat plasma by detection of albumin-adducts in vitro and in vivo - Tamara Kranawetvogl; Andreas Kranawetvogl; Lisa Scheidegger; Timo Wille; Dirk Steinritz; Franz Worek; Horst Thiermann; Harald John (Archives of Toxicology, 2023)
VX is a highly toxic organophosphorus nerve agent that reacts with a variety of endogenous proteins such as serum albumin under formation of adducts that can be targeted by analytical methods for biomedical verification of exposure. Albumin is phosphonylated by the ethyl methylphosphonic acid moiety ( EMP ) of VX at various tyrosine residues. Additionally, the released leaving group of VX, 2-(diisopropylamino)ethanethiol ( DPAET ), may react with cysteine residues in diverse proteins. We developed and validated a microbore liquid chromatography-electrospray ionization high-resolution tandem mass spectrometry (µLC-ESI MS/HR MS) method enabling simultaneous detection of three albumin-derived biomarkers for the analysis of rat plasma. After pronase-catalyzed cleavage of rat plasma proteins single phosphonylated tyrosine residues (Tyr- EMP ), the Cys 34 (- DPAET )Pro dipeptide as well as the rat-specific LeuProCys 448 (- DPAET ) tripeptide were obtained. The time-dependent adduct formation in rat plasma was investigated in vitro and biomarker formation during proteolysis was optimized. Biomarkers were shown to be stable for a minimum of four freeze-and-thaw cycles and for at least 24 h in the autosampler at 15 °C thus making the adducts highly suited for bioanalysis. Cys 34 (- DPAET )Pro was superior compared to the other serum biomarkers considering the limit of identification and stability in plasma at 37 °C. For the first time, Cys 34 (- DPAET )Pro was detected in in vivo specimens showing a time-dependent concentration increase after subcutaneous exposure of rats underlining the benefit of the dipeptide disulfide biomarker for sensitive analysis.